"Positive parochialism", local belonging and ecological concerns: Revisiting Common Ground's Parish Maps project. Issue 2 (24th December 2018) - Devine‐Wright, Patrick; Smith, Jos; Batel, Susana
Abstract : Scepticism about the value of parochialism and local belonging has been a persistent feature of geographical scholarship, which has advocated a relational account of place and a cosmopolitan worldview. This paper revisits the Parish Maps project that was instigated in 1987 by UK arts and environment charity Common Ground, which led to the creation of thousands of maps across the UK and beyond, and was appraised in 1996 by Crouch and Matless in this journal. Drawing on archival materials and in‐depth interviews, we examine the legacy of the project. We argue that Common Ground's vision for Parish Maps represents a "positive parochialism" that confidently asserts the validity of the parish without retreating towards insularity. We complicate this by revealing diverse ways that communities took up Common Ground's vision. We conclude by arguing that the view of parochialism manifest by Parish Maps offers a foundation for ecological concern that remains relevant today, with places offering the potential for solidarities that bring together local and incomer. This "positive parochialism" disturbs assumptions that local attachments are necessarily exclusive and indicates the unresolved challenge of finding ways to realise the value of affect and creative environmental engagement in wider policy and land‐use planning. Abstract : Scepticism about the value of parochialism and local belonging has been a persistent feature of geographical scholarship. This paper revisits the Parish Maps project that was instigated in 1987 by UK arts and environment charity Common Ground, and was appraised in 1996 by Crouch and Matless in this journal. Drawing on archival materials and in‐depth interviews, we conclude that the positive view of parochialism manifest by Parish Maps offers a foundation for ecological concern that remains relevant today, disturbs assumptions that local attachments are necessarily exclusive and indicates the unresolved challenge of finding ways to realise the value of affect and creative environmental engagement in wider policy and land‐use planning.